Pelatihan Manajemen Perpustakaan Desa Bagi Pemuda Karang Taruna Desa Binor Paiton Probolinggo - Farhan Farhan; Ali Ba’aly; Alif Rahman Ardiyansah; Dian Hidayatullah Farchani; Muhammad Fajar Danuarta (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
This article contains the results of service regarding village library management training for youth in Binor village, Paiton sub-district, Probolinggo district, East Java. The existence of a village library next to the mosque with ample parking is a good opportunity for the village library to optimize library management. The educated young people of Binor village also have the potential to develop human resources in making a more real contribution to their village in supporting the human development index (HDI), both in educational, cultural, religious and other aspects. In the educational aspect, young people from Karang Taruna can be optimized to support the reading and writing literacy program in optimizing the management of the 'Rohiqul Ilmi' village library in Binor village, but not all village youth are interested and interested in optimizing the village library. This is the reason for the Nurul Jadid University student service carried out between August and October 2023 which is focused on supporting the village library management program. This service uses the participatory action research (PAR) method, to collect data, analyze problems, formulate solutions, and implement corrective actions. The result; (1) Service takes place synergistically in the same paradigm by reviewing relevant literature in the concept of village library management; (2) establishing a stronger partnership with the involvement of the Nurul Jadid University community in encouraging village youth to be aware of literacy; and (3) supporting the National Library program in creating Indonesian reading ambassadors (DBI) in the regions, especially through the Binor village library, Paiton.